Efficacy and safety of Guizhi-Shaoyao-Zhimu decoction in the treatment of rheumatoid arthritis: A protocol for systematic review and meta-analysis. Issue 9 (5th March 2021) - Ye, Jing; Li, Renliang; Hu, Ziyi; Zhang, Ping; Liu, Liangji
Abstract: Background: Rheumatoid arthritis (RA) is a significant public health problem associated with a substantial burden of functional disability. The Guizhi-Shaoyao-Zhimu decoction (GSZD), a traditional medicine, has been used in China for a long time to treat RA. This study aimed to systematically investigate the efficacy and safety of GSZD in the treatment of RA. Methods: We will search the electronic databases of PubMed, Embase, the Cochrane Library, China National Knowledge Infrastructure, the Chongqing VIP Chinese Science and Technology Periodical Database, Wanfang Database, and China Biomedical Literature Database, and also manually search the Chinese Clinical Trial Register and unpublished studies or references, with the establishment up to February 2021. According to the inclusion and exclusion criteria, we will screen the literature, and the data are extracted independently by the 2 researchers. We will collect RCTs of GSZD in the treatment of RA. RevMan5.3 will be used for statistical analysis. According to the Grades of Recommendation, Assessment, Development, and Evaluation (GRADE), we will appraise each outcome quality evidence. Results: We will publish the results in a peer-reviewed journal. Conclusion: We will evaluate the efficacy and safety of GSZD in treating RA. Unique INPLASY number: INPLASY2020120147.